A particle with mass $m$ travels with speed $v_0$ and angle $\theta$ compared to the horizontal ground. Air resistance given as $F_R = -m \alpha v$, where $v$ is the particle's speed, is working against the projectile.

The particle's motion is described as

$$\frac{{dv_x} }{dt} + \alpha v_x = 0$$

$$\frac{{dv_y} }{dt} + \alpha v_y = -g$$


$$v_x = \frac{{dx} }{dt}$$

$$v_y = \frac{{dy} }{dt}$$

Show that the particles position is given as

$$ x(t) = \frac{{1} }{\alpha}(v_0 \cos \theta)(1-e^{-\alpha t})$$ $$ y(t) = \frac{{1} }{\alpha}(v_0 \sin \theta + \frac{g}{\alpha})(1-e^{-\alpha t}) - \frac{g}{\alpha}t$$

I understand how to set up the equations and do the integrals (at least a part of it) and get the following result:

$$ x(t) = \frac{{1} }{\alpha}(1-e^{-\alpha t})$$

What I don't understand is where the $v_0 cos \theta$ is coming from. I'm thinking it has something to do with decomposing forces in $x$ and $y$ direction, but I can't seem to work it out and where it goes in the equation.

(I haven't started with $y(t)$ yet).


closed as off-topic by John Rennie, Kyle Kanos, Aaron Stevens, Thomas Fritsch, stafusa Aug 30 at 7:40

This question appears to be off-topic. The users who voted to close gave this specific reason:

  • "Homework-like questions should ask about a specific physics concept and show some effort to work through the problem. We want our questions to be useful to the broader community, and to future users. See our meta site for more guidance on how to edit your question to make it better" – John Rennie, Kyle Kanos, Aaron Stevens, Thomas Fritsch, stafusa
If this question can be reworded to fit the rules in the help center, please edit the question.

  • $\begingroup$ What I don't understand is where the $v_0\cos\theta$ is coming from. From the initial conditions. $\endgroup$ – Gert Aug 29 at 14:27
  • 1
    $\begingroup$ $v_{x,0}=v_0\cos\theta$, $v_{y,0}=v_0\sin\theta$ $\endgroup$ – Gert Aug 29 at 15:50

I think, you forgot to add the integration constant. Integration of ${dv_x \over dt}+\alpha v_x=0$ gives $ln {v_x}=\alpha t+c_0$. After some algebraic manipulation we can write $v_x=Ae^{\alpha t}$, where $A=e^{c_0}$, and applying the initial condition gives $A=v_{x0}$ and from component decomposition we know $v_{x0}=v_0 cos \theta $. So now we're left with the following differential $eq^n$-$${dx \over dt}=v_0 cos \theta e^{ \alpha t}$$ whose $sol^n$ is $x(t)={1 \over \alpha} v_0 cos \theta e^{\alpha t}+c_1$. Applying the initial condition $x=0$ at $t=0$ , we get $c_1= -{1 \over \alpha}v_0 cos \theta$. Substituting it in the $x(t)$ expression you'll get your desired expression for $x(t)$.


Not the answer you're looking for? Browse other questions tagged or ask your own question.